Ignacio Andereggen, Zelmira Seligmann, Martín Echavarría y Gerardo Echevarren, La psicología ante la gracia. Ediciones de la Universidad Católica Argentina. Buenos Aires 1997. 413 páginas - Ferro Terrén, José Ignacio (1998)
Fil: Ferro Terrén, José Ignacio. Pontificia Universidad Católica Argentina; Argentina